Bagriy O.V. The influence of the internal Coulomb friction on the deformation of composite materials with low of connectivity. - Багрій, О.В. (Problems of Tribology, 2014)
In work presents the results of experimental researches of a wide class of composite materials with low connectivity, such as concrete, mortar, natural soils, technical ceramic products and others, on the regularities of deformation and failure of which significantly affects the internal friction. This class of materials have a significantly higher strength when working in compression than in distension. The growth of shear resistance with increasing values of compressive stress is interpreted as a sign of the internal Coulomb friction in the limit and in the prelimit stage of deformation. The purpose of research is to study the influence of the internal Coulomb friction on deformation of composite materials with a low connectivity in the limit stage of deformation. The results of the experiments are processed in the form of dependencies between the invariants of the tensors of the stress and strain.